2007
DOI: 10.1029/2006jc003798
|View full text |Cite
|
Sign up to set email alerts
|

El Niño Modoki and its possible teleconnection

Abstract: [1] Using observed data sets mainly for the period 1979-2005, we find that anomalous warming events different from conventional El Niño events occur in the central equatorial Pacific. This unique warming in the central equatorial Pacific associated with a horseshoe pattern is flanked by a colder sea surface temperature anomaly (SSTA) on both sides along the equator. empirical orthogonal function (EOF) analysis of monthly tropical Pacific SSTA shows that these events are represented by the second mode that expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

133
2,280
4
64

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 2,338 publications
(2,574 citation statements)
references
References 86 publications
(166 reference statements)
133
2,280
4
64
Order By: Relevance
“…Both findings agree well with those of Kao and Yu (2009), but the spatial pattern of the EEOF8 and EEOF9 El Niño does not resemble the horseshoe pattern found in that paper. However, the CP Niño composites of Kug et al (2009) and Ashok et al (2007) do not show a pronounced horseshoe pattern either, but a warm anomaly centered at about 1708W (i.e., 208 farther west than for our EEOF8 and EEOF9).…”
Section: Correlations and Effects Of Enso Cyclicitymentioning
confidence: 61%
See 2 more Smart Citations
“…Both findings agree well with those of Kao and Yu (2009), but the spatial pattern of the EEOF8 and EEOF9 El Niño does not resemble the horseshoe pattern found in that paper. However, the CP Niño composites of Kug et al (2009) and Ashok et al (2007) do not show a pronounced horseshoe pattern either, but a warm anomaly centered at about 1708W (i.e., 208 farther west than for our EEOF8 and EEOF9).…”
Section: Correlations and Effects Of Enso Cyclicitymentioning
confidence: 61%
“…Although there is no one-to-one relationship between the Seychelles dome SST variations and ENSO, a better understanding of this connection will provide a valuable additional ingredient for ENSO prediction at longer lead times and for understanding the behavior of ENSO on longer time scales. It would be interesting to investigate whether the frequent occurrence of CP El Niños in recent decades (Ashok et al 2007) is linked to the strong warming of the southwestern IO since the 1970s. If so, the southwestern IO temperature trends might also influence the changes in ENSO under global warming.…”
Section: Summary Discussion and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been increasingly recognized that there exists at least one more type of ENSO that onsets, develops, and decays locally in the equatorial central Pacific (Larkin and Harrison 2005;Yu and Kao 2007;Ashok et al 2007;Kao and Yu 2009;Kug et al 2009). This type of ENSO is often referred to as the central Pacific (CP) ENSO, while the conventional type of ENSO is referred to as the eastern Pacific (EP) ENSO.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have revealed that the CP ENSO can affect global and regional climate differently from the EP ENSO (e.g., Larkin and Harrison 2005;Hu et al 2012;Yu et al 2012b). The CP ENSO has occurred more frequently in the past few decades (Ashok et al 2007;Kao and Yu 2009;Kug et al 2009). The intensity of El Niño in the central Pacific region, for example, has doubled in the past three decades (Lee and McPhaden 2010), and the El Niño events in the twenty-first century so far have been mostly of the CP type (Yu et al 2012b).…”
Section: Introductionmentioning
confidence: 99%